1821 Me. Laws 352-53 - (:unkn) unknown (My University, 1821)
ch. 76, § 1 (1821): to cause to be staid and arrested, all affrayers, rioters, disturbers or breakers of the peace, and such as shall ride or go armed offensively, to the fear or terror of the good citizens of this State, or such others as may utter any menaces or threatening speeches;
Keywords: GOING ARMED